Devosi kepada Maria dalam Pendidikan Iman Kristosentris: Antara Penghormatan dan Tantangan Kristologis (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This article aims to explain the correct practice of devotion to Mary in the light of Christ-centered faith, which is a faith centered on Jesus Christ as the one and only mediator and savior. The main issue discussed is the tendency of some Catholics to give excessive devotion to Mary, which risks diverting focus from Christ. This study employs a theological and doctrinal approach by tracing the Church's teachings on honoring Mary, particularly through the distinction between latria, dulia, and hyperdulia. The study's findings indicate that proper devotion to Mary is rooted in a relationship with the Holy Trinity and guides the faithful to increasingly know, love, and emulate Christ. Conversely, disproportionate forms of devotion may lead to misunderstandings or deviations in faith practices. The implications of this research emphasize the Church's role in providing adequate catechesis, so that devotion to Mary remains balanced, leading the faithful to Christ through Mary and in Mary, while deepening the understanding of Trinitarian theology in the daily lives of Christians.